Hubungan Kepuasan Kerja dengan Retensi Staf Rumah Sakit di Provinsi Sulawesi Barat Tahun 2017 (Analisis Data Risnakes 2017) - Nadila Damayanti; Fajar Ariyanti (HEALTH CARE : JURNAL KESEHATAN, 2021)
Job satisfaction and retention are important factors for an organization in determining its success, this is because job satisfaction and retention can affect the performance of an employee where the employee's performance itself has an important role for the success of an organization's performance. This study aims to determine the relationship between job satisfaction and retention of hospital staff in West Sulawesi Province in 2017. This study used a cross sectional study design. The data in this study used secondary data from Risnakes 2017 with a sample of 244 respondents. Data analysis was performed using univariate and bivariate analysis. In the bivariate analysis using the Chi-square test with a CI 95% and a degree of significance of 5%. The results showed that the hospital staff who felt satisfied was 51.2% and the hospital staff who wanted to keep working were 85.2%. The results of the Chi-Square test obtained a p-value of 0.011 (p-value <0.05) so that the conclusion of this study is that job satisfaction has a significant relationship with retention of hospital staff in West Sulawesi Province in 2017. It is recommended for all hospitals in the Province West Sulawesi, in order to improve human resource management, should increase monitoring and evaluation activities, review job satisfaction and retention factors, and use related studies as references in implementing strategies to increase job satisfaction and retention.